Microsoft Office: Introductory concepts and techniques - Gary B Shelly (Boyd and Fraser, 1995)
This book consists of an introduction to computers, two projects on Microsoft Windows 3.1, an introduction to Microsoft Office, three projects each on the four Microsoft applications for Windows: Word 6, Excel 5, Access 2, and PowerPoint 4, and a project on object linking and embedding (OLE).